2020
DOI: 10.3389/fneur.2020.00271
|View full text |Cite
|
Sign up to set email alerts
|

MR-Guided Focused Ultrasound Central Lateral Thalamotomy for Trigeminal Neuralgia. Single Center Experience

Abstract: Background: Trigeminal neuralgia (TN) is a recognized pain condition the treatment of which can be very challenging. Various surgical interventions can be applied in cases of therapy-resistance to drug treatments. The central lateral thalamotomy (CLT) against neurogenic (or neuropathic) pain is based on multiarchitectonic histological as well as physiopathological studies, and integrates the nucleus in a large thalamocortical (TC) and corticocortical network responsible for the sensory, cognitive and affective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 34 publications
(68 reference statements)
0
23
0
Order By: Relevance
“…In turn, this would argue in favor of earlier surgical intervention in TN, which has been suggested to produce more durable pain relief ( 37 ). Furthermore, the functional networks identified in the present study may serve as potential pre-operative biomarkers of surgical outcome for TN and may also represent potential neurosurgical targets for TN or other pain conditions ( 38 40 ). We are currently carrying out further studies in which functional connectivity of the limbic system is compared between short-duration and longer-duration TN patients, and longitudinal studies in which functional connectivity is evaluated before and after TN surgery, in order to better understand the impact of limbic networks on treatment-resistance, the utility of limbic network connectivity as a biomarker of surgical outcome, and the extent to which altered limbic networks can actually be normalized by surgical intervention.…”
Section: Discussionmentioning
confidence: 90%
“…In turn, this would argue in favor of earlier surgical intervention in TN, which has been suggested to produce more durable pain relief ( 37 ). Furthermore, the functional networks identified in the present study may serve as potential pre-operative biomarkers of surgical outcome for TN and may also represent potential neurosurgical targets for TN or other pain conditions ( 38 40 ). We are currently carrying out further studies in which functional connectivity of the limbic system is compared between short-duration and longer-duration TN patients, and longitudinal studies in which functional connectivity is evaluated before and after TN surgery, in order to better understand the impact of limbic networks on treatment-resistance, the utility of limbic network connectivity as a biomarker of surgical outcome, and the extent to which altered limbic networks can actually be normalized by surgical intervention.…”
Section: Discussionmentioning
confidence: 90%
“…Drug-resistant trigeminal neuralgia is a debilitating pain condition that often is treated by surgery. In such cases, recently, it has been shown that tcMRgFUS bilateral central-lateral thalamotomy effectively treats patients affected by drug-resistant trigeminal neuralgia, with 63% of good outcomes at three months, 88% at 1 year and 100% at last follow-up with no adverse events [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding clinical applications of focused ultrasound, it has been recently demonstrated that tcMRgFUS postero-central lateral thalamotomy is an effective treatment of drug-resistant chronic neuropathic pain and trigeminal neuralgia [ 40 ]. In contrast, local MRgFUS ablation effectively treats pain related to lumbar bone metastases [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Jeanmonod et al focused on the use of MRI-guided focused ultrasound CLT albiet more specifically for trigeminal neuralgia ( 41 ). Eight patients with a mean age of 62 ± 12 years and a mean symptom duration of 17 ± 12 years were treated.…”
Section: Central Lateral Thalamotomymentioning
confidence: 99%